Routledge Companion to Audiences and the Performing Arts (Taylor & Francis, 2022)
The Routledge Companion to Audiences and the Performing Arts represents a truly multi-dimensional exploration of the inter-relationships between audiences and performance. This study considers audiences contextually and historically, through both qualitative and quantitative empirical research, and places them within appropriate philosophical and socio-cultural discourses. Ultimately, the collection marks the point where audiences have become central and essential not just to the act of performance itself but also to theatre, dance, opera, music and performance studies as academic disciplines. This Companion will be of great interest to academics, researchers and postgraduates, as well as to theatre, dance, opera and music practitioners and performing arts organisations and stakeholders involved in educational activities.
Deakin University
English
Keywords: Dance; Other performing arts; Psychology; Theatre studies; audience, performance, theatre, dance, opera, music, history, arts management, cultural policy studies, sociology